Teachers’ knowledge and attitudes toward inclusive education for children with autism in mainstream schools - Alassaf, Mohammed Abdulrhman (Frontiers in Education, 2025)
BackgroundInclusive education is a global priority aimed at ensuring equitable learning opportunities for all students, including those with autism spectrum disorder (ASD). Teachers’ knowledge and attitudes play a pivotal role in the successful implementation of inclusive practices. In Saudi Arabia, limited research has explored these dimensions among special education teachers.ObjectiveThis study aimed to assess the knowledge and attitudes of special education teachers in Riyadh toward inclusive education for children with autism in mainstream schools and to identify key demographic predictors influencing these variables.MethodsA descriptive cross-sectional design was employed. A total of 321 special education teachers were recruited using a convenience sampling technique. Data were collected using a structured, self-administered questionnaire comprising three sections: socio-demographic data, a 15-item knowledge scale, and a 15-item attitude scale. Descriptive statistics, independent samples t-tests, ANOVA, and multiple linear regression analyses were performed using SPSS, with a significance level set at p < 0.05.ResultsFindings revealed that teachers demonstrated a moderate level of knowledge (M = 3.29) and attitudes (M = 3.48) toward inclusive education. Significant differences were observed based on gender, age, educational qualification, teaching experience, and previous autism-related training. Regression analyses showed that female gender, higher educational qualifications, longer teaching experience, and prior autism training were significant predictors of both higher knowledge and moderate attitudes (p < 0.05).ConclusionWhile teachers exhibited generally supportive views of inclusive education, key knowledge gaps and structural challenges remain. Targeted professional development and institutional support are essential to enhance the capacity of teachers to effectively include children with autism in mainstream settings.